2008
DOI: 10.1002/dvg.20445
|View full text |Cite
|
Sign up to set email alerts
|

Early crest animals and the insight they provide into the evolutionary origin of craniates

Abstract: Summary: The Cristozoa (also known as crest animals) are established as representing the animals containing neural crest and its derivatives, constituting all known craniates and their immediate precraniate precursors. The precraniate crest animals all are extinct and preserved only in Early Cambrian strata of Yunnan (southwestern China). Fine anatomical details of Haikouella and the slightly more advanced species Yunnanozoon exhibit many characters unique to vertebrates, but they lack a skull and most other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 66 publications
(95 reference statements)
2
39
0
1
Order By: Relevance
“…Recent paleontological analysis of cristozoan fossils such as Haikouella lanceolata and Yunnanozoon lividum suggests a precraniate history of 'crest animals'. These fossils are characterized by paired gill rays and jointed, widely spaced branchial arches, but do not possess a skull (Chen, 2008;Chen et al, 1999;Holland and Chen, 2001;Mallatt and Chen, 2003). Although many structures directly involved in prey capture have been shown to derive from NC, the embryonic origin of the new, expanded respiratory organ, which according to the recent paleontological interpretation seems to predate the appearance of the skull, has not been investigated.…”
Section: Nc-driven Expansion Of the Respiratory Surface At The Protocmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent paleontological analysis of cristozoan fossils such as Haikouella lanceolata and Yunnanozoon lividum suggests a precraniate history of 'crest animals'. These fossils are characterized by paired gill rays and jointed, widely spaced branchial arches, but do not possess a skull (Chen, 2008;Chen et al, 1999;Holland and Chen, 2001;Mallatt and Chen, 2003). Although many structures directly involved in prey capture have been shown to derive from NC, the embryonic origin of the new, expanded respiratory organ, which according to the recent paleontological interpretation seems to predate the appearance of the skull, has not been investigated.…”
Section: Nc-driven Expansion Of the Respiratory Surface At The Protocmentioning
confidence: 99%
“…These paired bones accommodating the inner ear are considered to be a novelty of craniates and are absent in early crest animals (Chen, 2008;Gross and Hanken, 2008a;Mallatt and Chen, 2003). Studies in birds and mammals have shown a NC contribution to the otic capsule (Le Lièvre, 1978;O'Gorman, 2005;Noden, 1983).…”
Section: Nc Contribution To Cranial Skeletal Elements and Barbels In mentioning
confidence: 99%
“…These are considered by many to be chordates or close to them [31,32], but there are other possibilities [33-35]. Yunnanozoans have a dorsal sail-like structure that is apparently cuticularized and at least partially articulated.…”
Section: General Anatomy and Mode Of Life: Some Conjecturesmentioning
confidence: 99%
“…During the transition from invertebrates to vertebrates, the central nervous system (CNS) has undergone a series of striking changes including the dramatic increase of neuron number and the emergence of the tripartite brain with telencephalon (Williams and Herrup, 1988;Holland and Holland, 1999;Chen, 2008;Holland and Short, 2008). These changes are thought to be founded upon novel gene functions and the expansion of regulatory networks (Davidson and Erwin, 2006).…”
Section: Introductionmentioning
confidence: 98%